Analisis Keragaman Produk dan Keamanan terhadap Minat Beli pada Marketplace Sociolla di Surabaya - Aliyah, Siti Maslikhatun; Purwanto, Sugeng; Ariescy, Reiga Ritomiea (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The rapid development of the internet currently has security threats to online transactions so that it becomes a challenge for companies to maintain consumer buying interest, one of which is by providing security guarantees and offering a variety of products. This research was conducted with the aim of analyzing the effect of product diversity and safety on consumer buying interest at the Sociolla marketplace in Surabaya. The approach used is quantitative with a purposive sampling technique of 117 respondents who know the Sociolla marketplace and are domiciled in Surabaya. The software used in the data analysis process is SmartPLS. The final results of the research show that product diversity and safety make a positive contribution to consumer buying interest. Keywords: product diversity; purchase intention; security